Through the looking glass: empowering youth community advisory boards in Tanzania as a sustainable youth engagement model to inform policy and practice - Chow, Dana Wai Shin; Goi, Angelina; Salm, Maeve F.; Kupewa, Juma; Mollel, Getrud; Mninda, Yassin; Ambonisye, Judith; Malongo, Alan; Ketang’enyi, Eunice; Sanga, Erica; Ngowi, Happyness; William, Robert; et al. (Frontiers in Public Health, 2024)
More young people are living in the world than ever before, 90% of whom reside in low and middle income countries (LMICs). To address their needs, it is critical to have sustainable youth engagement when determining policy and to advance effective implementation of youth-focused interventions. Youth Community Advisory Boards (CABs) are a sustainable mechanism to achieve this goal. This paper describes engagement with youth CAB members across four locations in Tanzania. To set youth CAB meeting agendas and priorities, we asked youth CAB members to write (using free text) the top five challenges faced by young people in their communities (highest to lower priority). The Google Forms survey link was presented at the May 2023 youth CAB meeting and disseminated through WhatsApp. The survey was completed by smartphone, tablet, or paper provided to the youth liaison for data entry. Results were translated from Swahili to English and coded using excel. Findings were then presented back to the youth CABs at the September 2023 meeting. At that meeting, youth CAB members were then asked to write (free text) potential solutions to the most commonly described challenges. The surveys had response rates of 90% (84/93) for challenges and 78% (71/93) for solutions. The number one reported challenge was unemployment and financial instability (45%). Gender based violence (13%), sexual reproductive health issues (8%), and alcohol and drug use (8%) were in the top four both by priority and frequency of report. Other important challenges included physical and mental health, malnutrition, relationships, education, and societal and environmental norms, among others. Solutions included job creation, improved education, expanded legal systems, youth-friendly health care services, and increased social support through peer networks and community support. The National Accelerated Action and Investment Agenda for Adolescent Health and Wellbeing (NAIA-AHW) 2021/22-2024/25 includes most, but not all, of these top challenges and solutions. Ensuring young people have a seat at the policy table is critical to effective youth-empowerment in health and other related programs. Including a youth CAB member to represent this collective in youth-related government activities is a sustainable model to achieve this goal.